2014
DOI: 10.1038/nchembio.1503
|View full text |Cite
|
Sign up to set email alerts
|

The role of distant mutations and allosteric regulation on LovD active site dynamics

Abstract: Natural enzymes have evolved to perform their cellular functions under complex selective pressures, which often require their catalytic activities to be regulated by other proteins. We contrasted a natural enzyme, LovD, which acts on a protein-bound (LovF) acyl substrate, with a laboratory-generated variant that was transformed by directed evolution to accept instead a small free acyl thioester, and no longer requires the acyl carrier protein. The resulting 29-mutant variant is 1000-fold more efficient in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
177
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(194 citation statements)
references
References 55 publications
10
177
0
Order By: Relevance
“…The native substrate of the acyl-transferase LovD is covalently bound to an acyl carrier protein, LovF, which also functions as an allosteric activator. LovD was subjected to nine rounds of directed evolution for altered substrate specificity, thermal stability, and tolerance to organic solvent to generate a biocatalyst for production of the drug simvastatin (37). Insight into whether increases in activity were related to allosteric regulation was gleaned from microsecond molecular dynamics simulations, which suggested that LovF promotes the stability of a closed and catalytically active conformation of LovD and that directed evolution identified mutations that increased activity in a similar fashion (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The native substrate of the acyl-transferase LovD is covalently bound to an acyl carrier protein, LovF, which also functions as an allosteric activator. LovD was subjected to nine rounds of directed evolution for altered substrate specificity, thermal stability, and tolerance to organic solvent to generate a biocatalyst for production of the drug simvastatin (37). Insight into whether increases in activity were related to allosteric regulation was gleaned from microsecond molecular dynamics simulations, which suggested that LovF promotes the stability of a closed and catalytically active conformation of LovD and that directed evolution identified mutations that increased activity in a similar fashion (37).…”
Section: Discussionmentioning
confidence: 99%
“…LovD was subjected to nine rounds of directed evolution for altered substrate specificity, thermal stability, and tolerance to organic solvent to generate a biocatalyst for production of the drug simvastatin (37). Insight into whether increases in activity were related to allosteric regulation was gleaned from microsecond molecular dynamics simulations, which suggested that LovF promotes the stability of a closed and catalytically active conformation of LovD and that directed evolution identified mutations that increased activity in a similar fashion (37). Our kinetic, structural, and spectroscopic data provide firm experimental support for a similar effect in TrpB, demonstrating that allosteric potential can be readily converted into catalytic activity through directed evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, structural and dynamic studies of dihydrofolate reductase have shown that mutations that affect millisecond-time-scale fluctuations lead to decreased rates of hydride transfer (36). Similarly, crystallographic analysis and microsecond-scale molecular-dynamics simulations have suggested that remote mutations in simvastatin synthase alter catalytic efficiency through conformational effects (37). Other examples include the demonstration of altered catalytic activity in conformational isomers of a catalytic antibody and the effects of distal mutations on HIV protease active-site conformation and catalytic activity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MD can help in the future to discern long range effects. In fact, it has been recently used to highlight the impact of distant mutations on active site preorganization in evolved enzymes [159,160]. Furthermore, proteins are dynamical entities organized in a network of correlated fluctuations whose changes can significantly affect binding at large distances [161].…”
Section: Protein-ligand Binding Redesignmentioning
confidence: 99%